pH-Responsive Polymer Nanomaterials for Tumor Therapy - Chu, Shunli; Shi, Xiaolu; Tian, Ye; Gao, Fengxiang (Frontiers in Oncology, 2022)
The complexity of the tumor microenvironment presents significant challenges to cancer therapy, while providing opportunities for targeted drug delivery. Using characteristic signals of the tumor microenvironment, various stimuli-responsive drug delivery systems can be constructed for targeted drug delivery to tumor sites. Among these, the pH is frequently utilized, owing to the pH of the tumor microenvironment being lower than that of blood and healthy tissues. pH-responsive polymer carriers can improve the efficiency of drug delivery in vivo, allow targeted drug delivery, and reduce adverse drug reactions, enabling multifunctional and personalized treatment. pH-responsive polymers have gained increasing interest due to their advantageous properties and potential for applicability in tumor therapy. In this review, recent advances in, and common applications of, pH-responsive polymer nanomaterials for drug delivery in cancer therapy are summarized, with a focus on the different types of pH-responsive polymers. Moreover, the challenges and future applications in this field are prospected.